Cellular angiofibroma of the vulva: case report with clinicopathological and immunohistochemistry study - Micheletti, Adilha Misson Rua; Silva, Ana Cristina Araújo Lemos da; Nascimento, Antonio Geraldo; Silva, Cléber Sérgio Da; Murta, Eddie Fernando Candido; Adad, Sheila Jorge (São Paulo Medical Journal, 2005)
CONTEXT: Cellular angiofibroma of the vulva is a rare tumor that was first described in 1997. It occurs in middle-aged women (average age: 47 years), has small size (< 3 cm) and well-cir-cumscribed margins. CASE REPORT: We describe a case in a 51-year- old woman whose preoperative diagnosis was confounded with Bartholin’s glandular cyst. The neoplasia was well delimited and made up of three characteristic components: fusiform cells forming small fascicles, numerous blood vessels and adipose tissue interspersed between the fusiform cells. The stroma cells were positive for vimentin and negative for CD34, protein S-100, actin and desmin. The differential diagnoses for this tumor include aggressive angiomyxoma, angiomyofibroblastoma, lipoma of fusiform cells, solitary fibrous tumor, perineurioma and leiomyoma.